PEMBERDAYAAN KADER KESEHATAN DALAM PENDAMPINGAN PASIEN DIABETES MELLITUS MELALUI PELATIHAN SENAM KAKI - Ratnawati, Ratnawati; Jumari, Jumari; Pratama, Eka Firmansyah; Falah, Fakhriatul (Jurnal Abdimas Bina Bangsa, 2024)
Background: Diabetes mellitus is not just a disease, but also a challenge to the quality of life. However, we can manage this disease and live healthier with consistent small steps. One of them is doing regular foot exercises. Objective: This community service increases public awareness of the importance of foot exercises for diabetics, providing education on the correct foot exercise techniques. Method: Community service was conducted on June 25, 2024, at the Dutohe Barat Village Office Hall, Kabila District, Bone Bolango Regency. Results: From the evaluation of the level of knowledge and skills of health cadres and families for screening non-communicable diseases (PTM) before the program, the average value was 33% and after the program, the data was 100% with an average increase of 67%. Meanwhile, the results of the evaluation of the knowledge and skills of target partners about foot exercises before the program, the average value was 38.4% and after the program, the data was 100% with an average increase of 61.6%. Conclusion: Foot exercise training was enthusiastically welcomed by cadres and diabetics.